ASPECTS OF SIZE AND GEOGRAPHY OF AFRICAN CYBERSPACE - Nwagwu, Williams; Ibitola, Tolulope (Malaysian Journal of Library and Information Science, 2010)
In this study, data on web links collected from 15 African countries, three with the highest Internet penetration in each of North, West, Central, East and South sub-regions were used to study the number and origins of links to Africa. The sample has a ratio of one Internet user per 12 persons. Altogether, all African countries generated a total of 124,047,702 Web pages and 30,546,967 inlinks to the pages, an average of about 0.25 links per page. The study sample constituted 28% of all the countries in the region, which generated 98,629,700 pages and 21,272,500 inlinks, an average of about 0.21 inlinks per page. South Africa ranked the highest in web pages and web links per population and also received the highest number of inlinks from other African and the G8 countries. However, Kenya linked other African countries more than the others. The study also found that population size does not relate to number of web pages, self-inlinks, and inlinks or penetration, but relates positively with number of Internet users. A major step in boosting use of Internet resources in Africa will be in developing policies that will encourage African countries to use information developed by other African countries.